Recognizing Foreign Object Debris (FOD): False Alarm Reduction Implementation - Talha Khan; Muhammad Alam; Kushairy Kadir; Zeeshan Shahid; MS. Mazliham; Sheroz Khan; Mohammad Miqdad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recognition of foreign object debris (FOD) on ruwanys is mandatory to avert the accidents and emergency. The accurate and precise estimation of FOD is very complex because of the intricated shape and their different tiny sizes as well which are noe easily visilble. For the prompt removal of the FOD from the runways a robust, accurate and precise system is badly needed. Therefore, in our research we have proposed a vigor system comprised of ultrasonic sensor and infrared images capturing device with a combination of fake alerts reduction algorithm based on infrared images distribution and morphological edge identification. After the segmentation and morphological processing, the decision a unifying divider was designed to identify the actual targets. Several approaches have been done for the detailed and rapid investigation of FOD. Testing and validation have proved that our proposed research performed well compared to the other techniques. In this research ultrasonic sensors results are integrated with the processed infrared images.